Synthesis of hydroxyapatite from fish bone (scomber scombrus) using thermal decomposition method / Suguna Jeganathan - Suguna, Jeganathan (2019)
ABSTRACT There are numerous methods that can be used to synthesise HAp using various costly precursors. Studies related to fish bone derived hydroxyapatite are very limited and are usually focused on the synthesis parameters rather than mechanical property evaluation. Therefore, the present study is aimed to develop a process to synthesize HAp from fish bones and to evaluate the mechanical properties of the derived HAp. Various calcination temperatures were studied to determine the optimum temperature to produce high purity HAp. As-synthesized HAp powder was evaluated in term of mechanical properties and morphology. The sinterability of compacted HAp powder was investigated between 800°C to 1200°C. The study found that synthesized HAp powder looked a needle-like shape, similar to that observed in the human bones. Sintered HAp was stable up 1000°C temperature, whereas beyond this point, HAp began to decompose to its secondary phase (α-TCP and β-TCP). A near density of 98% was achieved at 1000°C, thus the density start to decrease beyond to this temperature due to the decomposition of Hap to TCP. This can correlated with SEM images which showed in prominent pore isolation when increased sintering temperature resulted forming a less dense ceramic. HAp samples showed the highest hardness of 3.49 GPa at 1000°C. The Vickers hardness of sintered HAp was increase as the relative density increase.